2017
DOI: 10.1101/102699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Family history and APOE4 risk for Alzheimer’s Disease impact the neural correlates of episodic memory by early midlife

Abstract: Episodic memory impairment is a consistent, pronounced deficit in pre-clinical stages of late-onset Alzheimer's disease (AD). Individuals with risk factors for AD exhibit altered brain function several decades prior to the onset of AD-related symptoms. In the current event-related fMRI study of spatial context memory we tested the hypothesis that middle-aged adults (MA; 40-58yrs) with a family history of late onset AD (MA +FH ), or a combined +FH and apolipoprotein E ε4 allele risk factors for AD (MA +FH+APOE4… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 95 publications
7
10
0
Order By: Relevance
“…Our findings are consistent with our previous work on the influence of APOE4 on brain activity in middle-aged adults at risk of AD (Rajah et al, 2017) and are the first to identify recognition-related differences in brain-behavior relationships in asymptomatic older adults at risk of AD. These findings add a nuanced perspective to the study of neural processes associated with recollection vs. familiarity as well as the role of APOE4 on brain-behavior relationships in asymptomatic older adults with family history of AD, which remains poorly characterized (O'Donoghue et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are consistent with our previous work on the influence of APOE4 on brain activity in middle-aged adults at risk of AD (Rajah et al, 2017) and are the first to identify recognition-related differences in brain-behavior relationships in asymptomatic older adults at risk of AD. These findings add a nuanced perspective to the study of neural processes associated with recollection vs. familiarity as well as the role of APOE4 on brain-behavior relationships in asymptomatic older adults with family history of AD, which remains poorly characterized (O'Donoghue et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Behaviorally, we found that both -APOE4 and +APOE4 individuals performed well on neuropsychological tests as well as our episodic memory task, with greater MoCA scores in +APOE4 individuals. These results largely align with previous studies showing no significant behavioral differences in cognitive performance on the basis of APOE4 status in younger (Taylor et al, 2017) and healthy older adults of similar demographic background (Reas et al, 2019), as well as our previous work using a similar episodic memory task in middle-aged adults at risk of AD (Rajah et al, 2017). However, given the high sensitivity of the MoCA for detecting mild cognitive impairment (Pinto et al, 2019), lower MoCA performance among -APOE4 participants may support theories suggesting that carrying an APOE4 allele may paradoxically benefit cognitive function in early and midlife (Evans et al, 2014).…”
Section: Few Behavioral Group Differencessupporting
confidence: 92%
See 1 more Smart Citation
“…The study design is similar to that published previously. 33,34 Participants were scanned as they encoded an object and it's left/right spatial location on the screen. Forty-eight encoding stimuli were presented one at a time for 2000 msec with a variable inter-trial interval (ITI).…”
Section: B Cerebrospinal Fluid (Csf) Proteinsmentioning
confidence: 99%
“…In cognitively healthy individuals, APOE-e4 has been linked to vulnerabilities in spatial navigation 35 , executive function 36,37 and processing speed 38 and both APOE-e4 and FH to impairments in episodic memory 36,[39][40][41][42] . Furthermore, both APOE-e4 and FH are associated with changes in brain areas known to be affected in LOAD, such as posterior cingulate, parietal, prefrontal and temporal cortices including hippocampal and parahippocampal regions [43][44][45][46][47][48] . For instance, APOE-e4 carriers with a FH of LOAD had larger axial diffusivity in the uncinate fasciculus (UF), a pathway that connects temporal and prefrontal cortex regions 49 .…”
Section: Introductionmentioning
confidence: 99%